GeoMemories—A Platform for Visualizing Historical, Environmental and Geospatial Changes in the Italian Landscape - Salvatore Minutoli; Maurizio Tesconi; Andrea Marchetti; Anders Hast; Clara Bacciu; Matteo Abrate (ISPRS International Journal of Geo-Information, 2013)
The GeoMemories project aims at publishing on the Web and digitally preserving historical aerial photographs that are currently stored in physical form within the archives of the Aerofototeca Nazionale in Rome. We describe a system, available at http://www.geomemories.org, that lets users visualize the evolution of the Italian landscape throughout the last century. The Web portal allows comparison of recent satellite imagery with several layers of historical maps, obtained from the aerial photos through a complex workflow that merges them together. We present several case studies carried out in collaboration with geologists, historians and archaeologists, that illustrate the great potential of our system in different research fields. Experiments and advances in image processing technologies are envisaged as a key factor in solving the inherent issue of vast amounts of manual work, from georeferencing to mosaicking to analysis.